The late Givetian (Middle Devonian) ammonoid Epitornoceras Frech, 1902 from Argentina (southwestern Gondwana) - Allaire, Ninon (2024)
During the Early to Middle Devonian, southwestern Gondwana was characterized by circumpolar marine environments with striking phases of increased endemism and near absence of typical Paleozoic groups (mainly conodonts, graptolites and stromatoporoids), which defined the Malvinoxhosan (Malvinokaffric) Realm. One of these clades is the Ammonoida. They are extremely rare: only a few occurrences were reported in Bolivia and Argentina in deposits ranging from early Eifelian to early Frasnian. The taxonomy of the only Devonian ammonoid species known from Argentina, Tornoceras baldisi Leanza, 1968, was revised based on type material and new specimens from the type area (Chigua Formation, Precordillera, western Argentina). The stratigraphic polarity of the sedimentary succession was reinterpreted, and ammonoid fossils occur in the uppermost interval of the Chigua Formation. Tornoceras baldisi is herein assigned to the genus Epitornoceras Frech, 1902, and consequently a late Givetian age is proposed for those levels. These occurrences better constrain the age of the upper part of the Chigua Formation (Chavela Member), which is now considered younger than the Belén and Huamampampa formations from Bolivia and possibly coeval to the upper part of the Iquiri Formation. Although the ammonoids indicate a biogeographic dilution of the Malvinoxhosan signature during the late Middle Devonian, the realm is still recognizable on the basis of endemic trilobites as typical indicators.